ЖАҲОННИНГ ОЧИҚ АХБОРОТ РЕСУРСЛАРИ ТАҲЛИЛИ - Зиядуллаев, Д.Ш.; Зиёдуллаева, Г.Э.; Кутлимуратова, Г.А. (SCIENCE and SOCIETY, 2017)
Information service called the Open Source community is recognized as a major catalyst for the development of education and modern services. This is an open resource types, use, learning resources and the same software is used for different purposes.